Effect of Abdominal Girth and Vertebral Column Length in Spread of Spinal Anesthesia for Lower Limb Surgery: A Prospective Study - Bhattarai, Rupak; Sah, Parasmani; Chetry, Neelam; Dev, Rajeev; Sharma, Prabin; Pokharel, Anish (Journal of Nobel Medical College, 2024)
Background: Subarachnoid spread of local anesthetics is quite erratic and is determined by several factors. There is a high predictive for the spread of spinal anaesthesia in terms of abdominal girth and vertebral column length. Our study is designed to determine the effect of abdominal girth and vertebral column length with cephalad spread of spinal anaesthesia for a given dose of 0.5% hyperbaric bupivacaine in Nepalese patients. Materials and Methods: In this prospective observational study, a total 100 patients of ASA PS I-II, aged16-65 years and undergoing lower extremity surgery under spinal anesthesia were enrolled. 2.8 mL of 0.5% hyperbaric bupivacaine was injected intrathecally at L3-4 interspace in sitting position. Extent of sensory blockade was assessed for 60 min. Simple linear regression, multiple linear regression and Pearson’s correlation coefficient analysis were performed to determine the correlation between patient variables viz abdominal girth, vertebral column length, height, weight, body mass index and age and maximum sensory block height. Results: Abdominal girth and vertebral column length correlated significantly with the maximal sensory block height after intrathecal administration of a fixed dose of 0.5% hyperbaric bupivacaine by all the three statistical tools used. Conclusion: Abdominal girth and vertebral column lengthcorrelate significantly with the maximal sensory block height in Nepalese patients receiving a fixed dose subarachnoid block with 0.5% hyperbaric bupivacaine